MAKNA DAN KETERLIBATAN ORANG KRISTEN DALAM RITUAL PUNDUK SAHUR PADA MASA COVID-19 DI DESA TUMBANG TAMBIRAH, KALIMANTAN TENGAH: KAJIAN SOSIO-TEOLOGIS - Isabella Jeniva; Yolantya Widyasari (Harmoni, 2021)
The Punduk Sahur ritual is one of the religious rituals of the Kaharingan tribe which aims to gain welfare and protection from the Dayak ancestors,  which is believed to be able to keep the Dayak community away from dangers such as disease outbreaks. Surprisingly, in Tumbang Tambirah Village, Christians are also involved in carrying out the Punduk Sahur ritual and believe that through this ritual they can avoid the Covid-19 outbreak. The approach used in this research is qualitative method and descriptive type. Data collection techniques that will be used, namely the technique of observation, interviews, and literature study. This study applies a socio-theological study that aims to find out and describe how the process of organizing the Punduk Sahur ritual in the midst of the COVID-19 outbreak for the people of Tumbang Tambirah Village, and what factors are the involvement of Christians in the Punduk Sahur ritual in the midst of the COVID-19 outbreak in Tumbang Village. Tambirah, Central Kalimantan. This study found a finding that it can be concluded that Christians in Tumbang Tambirah Village take a dualistic attitude in the relationship between Christ and Culture